Resource management of distributed virtual machines. (31st July 2012) - Wang, Lizhe; Chen, Dan; Zhao, Jiaqi; Tao, Jie
Using Virtual Machines (VMs) as a computing resource within a Service Oriented Architecture (SOA) creates a variety of new issues and challenges. Traditionally parallel task scheduling algorithms only focus on handling CPU resources but with use of a VM there are many more resources properties to monitor and manage. The objective of this paper is to address these challenges of a multi–dimensional scheduling algorithm for VMs within a SOA. To do this we deploy a testbed of SOA environment with VMs that are capable of being registered, indexed, allocated, accessed and controlled by our new parallel task scheduling algorithms.